The Influence of Metal-Doped Graphitic Carbon Nitride on Photocatalytic Conversion of Acetic Acid to Carbon Dioxide - Sakuna, Pichnaree; Ketwong, Pradudnet; Ohtani, Bunsho; Trakulmututa, Jirawat; Kobkeatthawin, Thawanrat; Luengnaruemitchai, Apanee; Smith, Siwaporn Meejoo (Frontiers in Chemistry, 2022)
Metal-doped graphitic carbon nitride (MCN) materials have shown great promise as effective photocatalysts for the conversion of acetic acid to carbon dioxide under UV–visible irradiation and are superior to pristine carbon nitride (g-C3N4, CN). In this study, the effects of metal dopants on the physicochemical properties of metal-doped CN samples (Fe-, Cu-, Zn-, FeCu-, FeZn-, and CuZn-doped CN) and their catalytic activity in the photooxidation of acetic acid were investigated and discussed for their correlation, especially on their surface and bulk structures. The materials in the order of highest to lowest photocatalytic activity are FeZn_CN, FeCu_CN, Fe_CN, and Cu_CN (rates of CO2 evolution higher than for CN), followed by Zn_CN, CuZn_CN, and CN (rates of CO2 evolution lower than CN). Although Fe doping resulted in the extension of the light absorption range, incorporation of metals did not significantly alter the crystalline phase, morphology, and specific surface area of the CN materials. However, the extension of light absorption into the visible region on Fe doping did not provide a suitable explanation for the increase in photocatalytic efficiency. To further understand this issue, the materials were analyzed using two complementary techniques, reversed double-beam photoacoustic spectroscopy (RDB-PAS) and electron spin resonance spectroscopy (ESR). The FeZn_CN, with the highest electron trap density between 2.95 and 3.00 eV, afforded the highest rate of CO2 evolution from acetic acid photodecomposition. All Fe-incorporated CN materials and Cu-CN reported herein can be categorized as high activity catalysts according to the rates of CO2 evolution obtained, higher than 0.15 μmol/min−1, or >1.5 times higher than that of pristine CN. Results from this research are suggestive of a correlation between the rate of CO2 evolution via photocatalytic oxidation of acetic acid with the threshold number of free unpaired electrons in CN-based materials and high electron trap density (between 2.95 and 3.00 eV).